수술실 간호사의 방사선안전관리 지식, 태도 및 행위에 대한 연구 - 윤영숙(Young Suk, Yoon) (한국간호연구학회지, 2018)
Purpose : This study is to promote awareness to be exposed to radiation with identifying knowledge, attitude and behavior for radiation safety management of the operating room nurse. Methods : The subjects were 193 of the operating room nurse and this study performed a questionnaire survey 18 Feb. to 17 June, 2014. Results : Based on the level of knowledge for radiation safety management, 10.08±2.72 for the operating room nurse out of 15 points. Based on the level of attitudes for radiation safety management, 4.52±0.46 for the operating room nurse out of 5 points. Based on the level of behavior for radiation safety management, 3.11±1.05 for the operating room nurse out of 5 points. The result for checking the relation with knowledge, attitudes and behavior for radiation safety management, the knowledge has correlation with attitudes(r＝.27, p＜.001) and behavior(r＝.50, p＜.001) statistically. Conclusion : We believe that a variety of programs should be offered to provide knowledge on radiation safety management as a prerequisite for improving the level of radiation safety management behaviors by operating roon nurse. KCI Citation Count: 0